2018
DOI: 10.3892/etm.2018.6034
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα, hs-CRP and FcγR in diabetic nephropathy and drug intervention

Abstract: The aim of this study was to investigate the roles of AMP-activated protein kinase α subunit (AMPKα), hypersensitive C-reactive protein (hs-CRP) and Fcγ receptor (FcγR) in diabetic nephropathy and drug intervention effects. Sixty Sprague Dawley male rats were randomly divided into the control (n=30) and observation (n=30) groups. The model of type 2 diabetic nephropathy was established by high-fat and high-glucose diet and streptozotocin injection. The rats in the observation group were treated with baicalein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…HsCRP is an acute-phase index of microinflammator response that can activate the complement system in the body and enhance the leukocyte phagocytosis by binding to the chromatin and can play a regulatory role by stimulating cell activation [2, 27]. Chronic endothelial inflammation is a major risk factor in the occurring of diabetic complications and has a pathogenic role in the progression of DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HsCRP is an acute-phase index of microinflammator response that can activate the complement system in the body and enhance the leukocyte phagocytosis by binding to the chromatin and can play a regulatory role by stimulating cell activation [2, 27]. Chronic endothelial inflammation is a major risk factor in the occurring of diabetic complications and has a pathogenic role in the progression of DN.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines have been demonstrated as important factors in the development of microvascular diabetic complications, such as nephropathy [11, 28]. Previous findings have shown that hsCRP is an independent risk factor of obesity and T2DM and hs-CRP is closely related to DN [2, 29]. As we know, nuclear transcription factor-kappa B (NF- κ B) is active in inflammation and immune responses in human cells.…”
Section: Discussionmentioning
confidence: 99%